Factors Associated With Job Satisfaction of Frontline Medical Staff Fighting Against COVID-19: A Cross-Sectional Study in China - Yu, Xiaoyan; Zhao, Yuxin; Li, Yuxi; Hu, Chao; Xu, Huilan; Zhao, Xianmei; Huang, Jin (Frontiers in Public Health, 2020)
To investigate the job satisfaction of frontline medical staff who were sent to aid treatment in Hubei or were working in local designated hospitals and then analyze the associated influencing factors. Materials and Methods: A total of 455 medical staff who worked at the frontline of the prevention and control of COVID-19 in Hubei province was selected using simple random sampling. They were asked to fill out a self-developed general information questionnaire as well as the Minnesota Satisfaction Questionnaire (MSQ), from January to 10 March 2020. Results: The average job satisfaction score of the participants was 82.58 ± 11.11. The influencing factors included education (P = 0.002), years of work experience (P = 0.006), anti-epidemic work duration (P = 0.048), daily sleep duration (P <0.001), and the form of participation (P <0.001).The job satisfaction of frontline medical staff fighting against COVID-19 was at a "relatively decent" level, higher than that reported in previous surveys among medical staff. Relevant departments should further improve the job satisfaction of frontline medical staff by meeting their reasonable demands, strengthening the emergency response and practical operation training of junior staff, and ensuring their normal sleep and rest times.